2020
DOI: 10.3390/foods9121799
|View full text |Cite
|
Sign up to set email alerts
|

High Glucosinolate Content in Rocket Leaves (Diplotaxis tenuifolia and Eruca sativa) after Multiple Harvests Is Associated with Increased Bitterness, Pungency, and Reduced Consumer Liking

Abstract: Rocket (Diplotaxis tenuifolia and Eruca sativa) leaves delivered to the UK market are variable in appearance, taste, and flavour over the growing season. This study presents sensory and consumer analyses of rocket produce delivered to the UK over the course of one year, and evaluated the contribution of environmental and cultivation factors upon quality traits and phytochemicals called glucosinolates (GSLs). GSL abundance was positively correlated with higher average growth temperatures during the crop cycle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 35 publications
6
24
0
1
Order By: Relevance
“…The aim of this work was to show that the morphometric traits and GLSs profile were influenced both by the climatic conditions that characterized different plant growth stages and by the genotype taken into consideration [40,41]. In any case, further studies would be needed to better define the relationship between environmental conditions and GLSs profile.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this work was to show that the morphometric traits and GLSs profile were influenced both by the climatic conditions that characterized different plant growth stages and by the genotype taken into consideration [40,41]. In any case, further studies would be needed to better define the relationship between environmental conditions and GLSs profile.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that plants from both tanks will have similar sweetness. Bell et al [32] reported that consumers preferred rocket leaves from the first cut compared to leaves from successive cuts, and the result was associated with higher glucosinolate concentrations which increased the bitterness and peppery perceptions. Fallovo et al [12] observed that reduced sugar content was associated with increased nitrate content which was not evident in our case.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the consequences for human health are important, too. This Special Issue includes eleven research articles that cover research on the effect of pre-harvest factors on glucosinolates, their hydrolyzing enzymes, and the formation of volatile hydrolysis products [ 2 , 3 , 4 , 5 ]. Further topics include the linkage between glucosinolates and sensory aspects [ 2 , 6 , 7 ], and the effects of food preparation and follow-up reactivity [ 7 , 8 , 9 , 10 ].…”
mentioning
confidence: 99%
“…This Special Issue includes eleven research articles that cover research on the effect of pre-harvest factors on glucosinolates, their hydrolyzing enzymes, and the formation of volatile hydrolysis products [ 2 , 3 , 4 , 5 ]. Further topics include the linkage between glucosinolates and sensory aspects [ 2 , 6 , 7 ], and the effects of food preparation and follow-up reactivity [ 7 , 8 , 9 , 10 ]. Finally, two articles focus on the bioavailability and functional effects of isothiocyanates for human health [ 1 , 11 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation